Coping Strategy, Social Support, and Psychological Distress Among University Students in Jakarta, Indonesia During the COVID-19 Pandemic - Akbar, Zarina; Aisyawati, Maratini Shaliha (Frontiers in Psychology, 2021)
The COVID-19 pandemic has challenged the world for a year, where a study in China showed that the disease increased psychological distress among adolescents and college students, such as anxiety about the academic setback, economic effects, and impact on their daily life. However, a further study examining the impact of the disease on the mental health of students is required. Social support is the most vital psychosocial protective resource, where effective coping can reduce stress levels and prevent individuals from experiencing more severe psychological distress. Therefore, this study investigated the coping strategy, social support, and psychological distress among university students in Jakarta who are also the epicenter of COVID-19 in Indonesia. The psychological distress and coping strategy variable were measured through the Hopkins Symptoms Checklist-25 (HSCL-25) and the COPE Brief instrument, respectively. Meanwhile, the Multidimensional Perceived Social Support-12 instrument was used to measure the social support variable. The study was disseminated via an online form and the number of research subjects included 250 students who matched the research criteria, including DKI Jakarta domicile and active students registered in the area that were confirmed to be COVID-19 positive. According to the results, coping strategies and increased social support were significantly correlated with decreased psychological distress and may serve as the basis for interventions.